Infraestrutura escolar e formação: uma análise acerca da consciência cindida dos estudantes do ensino médio - Rodopoulos, Adriana Spacca Olivares (2017)
The present research, of the empirical type, has as a study object the issues related to the public school infrastructure as a formative resource. Considering that the students are the final users of the school equipment and premises, and that the school material and structural conditions have been treated, in the last years, as a non-relevant input towards the educational experience – due to the influence of the knowledge produced by the World Bank over Brazilian educational policies, which has been generating a systematic reduction over the investment rate in this area – the research question which guides this paperwork is: whether and to what extent are the students’ views towards the infrastructure as a formative resource aligned to the recommendations of the World Bank? Since this question encompasses the relationship between school infrastructure and formation, the research objectives were stated as following: (a) identifying the level of importance given by students to the role of the school infrastructure to their formation; and (b) verifying the students’ attributions to the concept of formation. In order to achieve these objectives, we collected the students’ answers from a patterned questionaire, which was applied to students aged 14 to 18 years old from a public technical school located in the metropolitan area of São Paulo. The results suggest that the students are more critical about the infrastructure as a formative resource, than about the concept of formation restricted to the preparation of the workforce. Thus, they seem to recognize the formative potential of the infrastructure, but they fail to overcome the predominant concept of formation. The theoretical referential that supports this research is the critical theory of society, specially the studies developed by Herbert Marcuse, Theodor W. Adorno, Max Horkheimer and Walter Benjamin, highlighting the ones related to the technological ideology, to the formation and to education